Pengaruh Trusting Beliefs Terhadap Intention to Purchase Dan Making Purchase Pada Sociolla - Khairunnisa, Edwina; Azhari, Muhammad; Hidyatulloh, Deden Syarief (Peneliti.net, 2023)
Technological developments in the world directly have an impact on the economic sector, especially electronic markets or e-commerce. The gross merchandise value of e-commerce in Indonesia has shown positive growth Since 2020, and is predicted to continue to increase until 2027. Health and beauty products are the most frequently purchased products in Indonesian e-commerce. One e-commerce that specifically sells beauty products is Sociolla. Sociolla offers beauty products with guaranteed originality directly from the beauty brand. This study aims to determine the effect of Sociolla user trust and intention to make purchases on Sociolla e-commerce. The benefit of this research is as a form of research contribution in the field of economics and becomes an illustration of phenomena that occur in Indonesian society. The method used is descriptive quantitative. The data source comes from a questionnaire distributed to a sample of the Indonesian beauty consumer population who buy beauty products online on the Sociolla platform. The data was processed using the SEM-PLS analysis tool using SmartPLS version 3.0 software. The results of the study show that competence and benevolence, which are the sub-variables of trust, have a significant and positive effect on intention. While integrity has no sifnificant influence on intention to purchase. Then intention to purchase has a positive and significant influence with post-purchase, but not with purchase.